2003
DOI: 10.1038/sj.bjc.6601158
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficiency of rhenium-188-HEDP in human prostate cancer skeletal metastases

Abstract: Rhenium-188-HEDP (Re generator, it is convenient for clinical therapeutic use with a short physical half-life of 16.9 h and a maximal b-energy of 2.1 MeV. We investigated the effect of 188 Re-HEDP on pain relief, analgesic intake and impairment of bone marrow function in 27 patients with bone metastases induced from prostate cancer. All patients were interviewed using a standardised set of questions before, and after therapy for 12 weeks. The patients were treated with 2700 -3459 MBq of 188 Re-HEDP. Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 21 publications
4
58
0
Order By: Relevance
“…There are single reports using 131 I-BDP3 (Eisenhut et al 1986) and yttrium-90 (Kutzner et al 1982). More recently, 117m Sn-DTPA (Atkins et al 1995) 188 Re-HEDP (Palmedo et al 2000;Liepe et al 2003b) and 188 Re-DMSA (Blower et al 2000) have been reported to be effective for bone pain palliation, but these agents were used only in clinical studies.…”
Section: Introductionmentioning
confidence: 95%
“…There are single reports using 131 I-BDP3 (Eisenhut et al 1986) and yttrium-90 (Kutzner et al 1982). More recently, 117m Sn-DTPA (Atkins et al 1995) 188 Re-HEDP (Palmedo et al 2000;Liepe et al 2003b) and 188 Re-DMSA (Blower et al 2000) have been reported to be effective for bone pain palliation, but these agents were used only in clinical studies.…”
Section: Introductionmentioning
confidence: 95%
“…As recently Re 186 /Re 188 is also used e.g. in palliative treatment of bone metastases [24], similar applications may be expected for the rhenium analogues. The authors reporting the analogous picoline technetium complex [22] did not provide accurate structure parameters, but solved the oxidation state problem in a later report, completing physicochemical properties characterization for [XL 4 Tc-O-TcX 4 L] (X = Cl/Br, L = pyridine, 4-picoline, 3,5-lutidine) complexes.…”
mentioning
confidence: 89%
“…The Re1-Cl cis bond lengths are comparable (2.376(2)-2.385(2) Å). For comparison, in trans-ReCl 4 (py) 2 the Re IV -Cl bond length is 2.330 (1) Å, whereas Morrow[24] reported for K4 [Re 2 OCl 10 ] all Re-Cl bond lengths of 2.38(2) Å. The four pyridine ligands around the "Re III " centre are distributed in a propeller-like fashion.…”
mentioning
confidence: 96%
“…However, the average beta energy is considerably higher than that of samarium-153, and consequently the range is longer so that, at least theoretically, it is less sparing of the bone marrow. However, dosimetry from Re-188-HEDP, a much higher energy beta emitter, was shown to be within acceptable limits (Liepe et al, 2003). The dose ratio of bone to marrow is not particularly favorable for Re-186 and the compound is less stable in vivo than the other radiopharmaceuticals under discussion (Maxon et al, 1990;de Klerk et al, 1992).…”
Section: Rhenium-186 Hedpmentioning
confidence: 99%